Competitive sport shooting - Practical sport psychology - Lösel, H. (Eigenverlag, 1999)
Anxiety and overcoming anxiety Autogenous training, a measure used for competition Autogenous training in sport shooting Muscular relaxation (Jacobson), tonus relaxation (Stokvis) Desensitization, implosion therapy, behavioral therapy Music therapy Provoking anxiety Beta-blocker and psychopharaceuticals Complementary transaction between shooters and reference persons Individual psychostabilization Experimental medication Taking placebos Taking placebos: An amusing sample Sleep can be learned Smoking can be unlearned